AB0584 Utility of PET/CT scan for the diagnosis of aortitis. a study of 170 patients from a single center in a 6-year period. (15th June 2017) - Vegas-Revenga, N; Loricera, J; Prieto-Peña, D; Martínez-Rodríguez, I; Banzo, JI; Calderόn-Goercke, M; Calvo-Río, V; González-Vela, C; González-Vela, J; González-Gay, MΆ; Hernández, JL; Blanco, R
Abstract : Background: Aortitis is the inflammation of the aortic wall. This entity is often under-recognised due to its frequent presentation with non-specific symptoms. PET/CT scan represent a major breakthrough to establish an early diagnosis, but this is an expensive technique. Objectives: Our aim was to compare the baseline characteristics of patients with a suspicion of aortitis and positive results on PET/CT scan, and those with a negative result, in order to search for predictive factors, that improve the clinical probability of diagnosis aortitis by this imaging technique. Methods: Retrospective study on 170 patients and PET/CT scans ordered by suspicion of aortitis from a referral center from January 2010 to December 2016. According to a pre-specified protocol, the baseline epidemiological and clinical variables of patients with positive and negative PET/CT scans results for aortitis were reviewed. Distributions of categorical variables were compared by the Pearson Chi 2 or Fisher exact test. Quantitative variables were analyzing using the Student t test or Mann-Whitney U test as appropriate. Results: In 170 patients, PET/CT scans were performed due to clinical suspicion of aortitis, and were positive in 93 (54.7%) cases. Patients (113 women/57 men) had a mean age of 67.7±13.1 years (range, 20–90 years). One patient was excluded because missing clinical or laboratory data. The underlying diseases at the moment of ordering the PET/CT scan were: giant cell arteritis (GCA) (n=28), spondiloarthropaties (n=7), conectivopaties (n=6), Takayasu arteritis (n=3), ulcerative colitis (n=3), other condition (n=11). The remaining 111 patients did not have any underlying condition suggestive of aortitis. Two out of 170 patients suspected an infectious aortitis ( Brucella and Salmonella ); however, PET/CT was negative in both cases. Characteristics of patients with positive and negative PET/CT scans were summarized in the Table. Patients with GCA had a higher percentage of positive PET/CT scans, whereas they were negative more frequently in patients who did not have any condition suggestive of underlying aortitis. Only inflammatory low back pain and polymyalgic syndrome were significantly more frequent in patients with positive PET/CT scans. The remaining clinical and laboratory variables did not show differences between both groups. Conclusions: In this study, we have found that the presence of inflammatory low back pain and polymyalgic syndrome, especially in GCA patients, may have clinical relevance in ordering a PET/CT scan when aortitis was suspected. Disclosure of Interest: None declared